2012
DOI: 10.1007/s12551-011-0065-4
|View full text |Cite
|
Sign up to set email alerts
|

Proteoliposomes in nanobiotechnology

Abstract: Proteoliposomes are systems that mimic lipid membranes (liposomes) to which a protein has been incorporated or inserted. During the last decade, these systems have gained prominence as tools for biophysical studies on lipid-protein interactions as well as for their biotechnological applications. Proteoliposomes have a major advantage when compared with natural membrane systems, since they can be obtained with a smaller number of lipidic (and protein) components, facilitating the design and interpretation of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
17

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 171 publications
(222 reference statements)
1
38
0
17
Order By: Relevance
“…Garcia et al (2015) used electron spin resonance measurements along with spin labeled phospholipids to probe the possible dynamic changes prompted by the interaction of GPIanchored TNAP with model membranes. In this study, these authors showed that TNAP is probably close to the membrane surface, suggesting that this proximity can be related to the modulation of TNAP activity by the lipid composition of the vesicles, as previously reported (Bolean et al 2010(Bolean et al , 2011Ciancaglini et al 2012;Garcia et al 2015;Simao et al 2010a).…”
Section: What Are the Biomimetic Systems Of Mvs?supporting
confidence: 85%
“…Garcia et al (2015) used electron spin resonance measurements along with spin labeled phospholipids to probe the possible dynamic changes prompted by the interaction of GPIanchored TNAP with model membranes. In this study, these authors showed that TNAP is probably close to the membrane surface, suggesting that this proximity can be related to the modulation of TNAP activity by the lipid composition of the vesicles, as previously reported (Bolean et al 2010(Bolean et al , 2011Ciancaglini et al 2012;Garcia et al 2015;Simao et al 2010a).…”
Section: What Are the Biomimetic Systems Of Mvs?supporting
confidence: 85%
“…For example, MLVs may be sonicated or passed through a membrane with pores of nanometric dimensions (extrusion method) to form unilamellar vesicles that have properties very similar those of to natural membranes. Both the sonication and extrusion methods provide the energy required to break the various lamellae that initially formed and reorganize the system into uniform bilayers with controlled sizes of vesicles (Camolezi et al 2002;Ierardi et al 2002;Daghastanli et al 2004;Santos et al 2002Santos et al , 2005Rigos et al 2008;dos Santos et al 2009;Bolean et al 2010Bolean et al , 2011Simão et al 2010a, b;Ciancaglini et al 2012).…”
Section: Liposomesmentioning
confidence: 99%
“…Recentes estudos têm demonstrado que a função da TNAP no tecido ósseo consiste em hidrolisar PP i para manter uma concentração adequada deste inibidor da mineralização, de modo a assegurar uma mineralização óssea normal Millán, 2006;Ciancaglini, et al, 2010Ciancaglini, et al, , 2012Simão et al, 2010).…”
Section: Fosfatase Alcalina (Tnap)unclassified
“…Assim, diferentes formas da enzima (ligada à membrana, solubilizada com detergente ou tratada com PIPLC (fosfolipase C) apresentaram diferentes especificidades para os diversos substratos estudados, mostrando que a cinética da enzima é grandemente afetada pela presença tanto da âncora de fosfatidilinositol quanto de outros componentes da membrana celular (Ciancaglini et al, 2006;Simão et al, 2010;Bolean et al, 2010Bolean et al, , 2011Ciancaglini et al, 2012).…”
Section: Fosfatase Alcalina (Tnap)unclassified
See 1 more Smart Citation